The Correlation Analysis Between 4C Skill Components in High School Mobility System Material with GGE-JAS Learning Model - Ma'rifah, Amriyah Ummi; Marianti, Aditya; Isnaeni, Wiwi (Unnes Science Education Journal, 2024)
This research aims to analyze the correlation of 4C skill aspects based on students’ achievement in each aspect through GGE-JAS learning model. This research was conducted at SMA N 1 Tengaran, Semarang Regency with a quasi-experimental model and a non-equivalent group research design. The data collection method used was with test and non-test instruments. The results of this research in critical thinking skills in control class had an N-gain result of 0.36 in the low category and the experimental class was 0.53 in the medium category. This shows a striking difference before and after treatment in each class, so that the GGE-JAS model was effective. After the implementation of the GGE-JAS model in the experimental class, the achievement of critical thinking indicators was 73% in good category, collaboration skills was 83% in a very colaborative category, communication skills was 74.8% in a communicative category and creative thinking skills was 71.32% in creative category. The results of the correlation analysis stated that collaboration skills had a significant relationship with communication skills with t-value of 3.22 while creative thinking skills had a significant relationship with critical thinking skills with t-value of 2.04. The conclusion of this research is that GGE-JAS model is effective to improve students’ 4C skills in the mobility system material for class XI MIPA SMA N 1 Tengaran, Semarang Regency and students’ collaboration skills are significantly positive related to students’ communication skills, while students’ creative thinking skills have a significant positive relation with students’ critical thinking skills.